FACTORS INFLUENCING STRATEGY IMPLEMENTATION IN STATE CORPORATIONS IN KENYA A CASE OF COUNCIL OF LEGAL EDUCATION - Nyaga, Dinah Kathambi; Litunya, Dr. Rose (European Journal of Business and Strategic Management, 2018)
Purpose: This study sought to establish the factors influencing strategy implementation in state corporations in Kenya a case of council of legal education. Methodology: Descriptive research design was adopted for this study. The whole population formed part of the sample size due to the small size of the employees at the Council of Legal Education. Questionnaire was adopted as the research instrument for the study was subjected to pilot testing to identify its validity and reliability. Then data was cleaned and analyzed using SPSS Version 23. The findings were presented using tables, pie charts and bar graphs for further analysis and to facilitate comparison. Results: Based on the results, a significant awareness level of strategic implementation was established. The results found that a majority of the respondents were aware of the vision and mission represented by 90.7%. The researcher found that though the respondents strongly agreed that organizational structure significantly influenced strategy implementation; majority disagreed that the current organization structure supported the strategic plan. This is represented by 34.4%. Training and involvement of employees in development and implementation was found critical to successful implementation. A strong positive relationship between alignment of organization structure with business strategy and implementation of strategy was established (R=.907, F=24.16, P<0.01). Exactly 50% of the respondents agreed that periodic reporting of strategic implementation was done at the Council of legal Education. Timely evaluation and reporting the feedback to all employees was found essential communication in the implementation process. Unique Contribution to Theory, Policy and Practice: The study recommended the, review of the current organization structure at the Council of Legal Education, factoring reward and motivation, development of a clear chain of communication and involving all employees in development of strategic plan and implementation process.